The renewed TC12/ESIS technical committee - Risk analysis and safety of large structures and components. (November 2019) - Correia, José A.F.O.; De Jesus, Abílio M.P.; Muniz-Calvente, Miguel; Sedmak, Aleksandar; Moskvichev, Vladimir; Calçada, Rui
Abstract: The ESIS Executive Committee decided to nominate a new team for the leadership and management of the TC12/ESIS technical committee (TC), as well as update the TC name as "Risk Analysis and Safety of Large Structures and Components". In this paper, the new organization of the TC12/ESIS as well as the objectives and tasks, and forthcoming events are presented. In addition, this document has editorial purposes regarding the selected and published papers from the International Symposium on Risk Analysis and Safety of Large Structures and Component s (ISRAS-TC12) organized within of the "2 nd International Conference of Structural Integrity (ICSI)", which took place at Madeira Island, Portugal, on 4–7 September 2017. As guest editors and TC12/ESIS members, we hope the ISRAS-TC12 Special Issue provides a remarkable impact in the research related to fatigue, fracture, structural integrity, risk analysis and safety of complex structures and components. We also would like to express our gratitude to all authors for their contributions and to all reviewers for their generous work to guarantee the excellence of the papers. Finally, the guest editors would like to express a special thanks to Professor Richard Clegg, Editor-in-Chief of Engineering Failure Analysis journal, and to Elsevier staff for their support during the preparation of this issue.